ANALISIS AKUNTANSI PROGRAM MANFAAT PENSIUN PADA ENTITAS TANPA AKUNTABILITAS PUBLIK - Prasetya Adi; Amrie Firmansyah (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2018)
This study aims to review the practice of accounting application of pension programs in entities without public accountability. This research uses the object of pension program implemented by Waroeng SS. The research method used in this study using qualitative methods. The study was conducted during the period of March-June 2018. Interviews to informant was conducted on the second week of May 2018. The selection of informant was based on the knowledge capabilities associated with the information in this study. The informant in this research is the financial staff of Waroeng SS. This study concludes that the retirement / pension benefit accounting policy in Waroeng SS is implemented through a defined benefit plan that is independently managed by the internal Waroeng SS or can be referred to by the employer's pension fund. There are differences in the recording of liabilities on pension plans implemented by Waroeng SS and SAK ETAP Chapter 23 (2009). Furthermore, the pension fund managed by Waroeng SS which is still one with the management of the SS waroeng is contrary to regulations concerning pension funds, but does not conflict with SAK ETAP because SAK ETAP does not regulate related to the separation of funds between management and pension funds